Beneficial reward-to-risk action of glucosamine during pathogenesis of osteoarthritis. Issue 1 (December 2015) - Kang, Yeon-Ho; Park, Sujeong; Ahn, Chihyun; Song, Jinsoo; Kim, Dongkyun; Jin, Eun-Jung
Abstract Objective Glucosamine is widely used to improve the symptoms and to delay the structural progression of osteoarthritis. However, its efficacy in osteoarthritis has been controversial and its underlying mechanism of action remains unclear. The aim of this study was to investigate the effects of glucosamine and the underlying mechanisms in human chondrocytes. Methods Chondrocytes from normal human articular cartilage were treated with glucosamine (10–100 mM). Subsequently, cell death was analyzed by Annexin V staining and FACS and mitochondrial function was studied by measuring the mitopotential. Peroxisomal function was analyzed by BODIPY staining, and gene expression of PMP70 and acyl-CoA oxidase 1, by real-time PCR. Total lipids were analyzed by gas chromatography/mass spectrometry. Autophagy activation was determined by western blotting of beclin and light chain 3B. Autophagosome formation was analyzed by introduction of green fluorescent protein (GFP) LC3, and pexophagy was determined by introduction of mRFP-EGFP-SKL plasmids. Results Treatment of chondrocytes with glucosamine exerts exposure time-dependent dual effects on apoptosis/autophagy. Short time exposure of glucosamine to chondrocytes activated autophagy, pexophagy, and peroxidation. On the other hand, long time exposure of glucosamine had opposite effects, namely accumulation of very long chain fatty acids and peroxisomal dysfunction. Conclusion We highlight the dual role of glucosamine in apoptosis/autophagy in human chondrocytes depending on exposure time. Although further research is required to fully understand the dual effects of glucosamine, dosage and duration of glucosamine treatment are clear contributing factors towards the line of beneficial reward-to-risk action.